PENIGKATAN HASIL BELAJAR INDONESIA PADA MATERI KALIMAT SARAN MELALUI MODUL PEMBELAJARAN BAHASA INDONESIA KELAS III SD MUHAMADIYAH KEMIRI KAB. PURWOREJO - Siti Anisatun Nafiah; Luthfi Faridah (As-Sibyan, 2022)
This study aims to increase students' understanding of the Suggestion Sentence material and describe the increase in student cognitive learning outcomes through the Class III Indonesian Language Learning Module at Muhammadiyah Elementary School, Kemiri District, Purworejo Regency. The research method used class action research (PTK) using the Kurt Lewin model. . Data collection methods used are observation, tests, and interviews. Data analysis techniques by comparing the learning outcomes of cycles 1 and 2. The results showed that learning modules in learning Indonesian can improve student learning outcomes. It can be seen from the average score obtained in cycle I, which was 74.37. In cycle II the class average value was 82.5. Based on the results of the study, it can be concluded that the use of Indonesian language learning modules can improve student learning outcomes in Indonesian language learning subjects, especially the suggestion sentence material in class III Muhammadiyah Elementary School, Kemiri District, Purworejo Regency.